2012
DOI: 10.4317/jced.50590
|View full text |Cite
|
Sign up to set email alerts
|

Use of anesthetics associated to vasoconstrictors for dentistry in patients with cardiopathies. Review of the literature published in the last decade.

Abstract: Objective: The use of local anesthetics associated to vasoconstrictor agents in dentistry is thoroughly justified and is widely extended, but we cannot ignore the fact that anesthetic infiltration poses risk of complications throughout the dental treatment period. The objective of the present review is to document the reported effects the use of the local anesthetics most widely employed in dentistry, with or without association to vasoconstrictor agents may have in patients with any sort of cardiopathy. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…4 Dental local anesthetic solutions contain vasoconstrictors, for example, 2% lidocaine with 1:80,000 adrenaline (L þ AD) or 3% prilocaine with 0.03 IU/mL felypressin (P þ FP), are both commonly used in Japan and may potentially affect the cardiovascular condition. 5,6 L þ AD, which is one of the most frequently used anesthetics during dental treatment, is known to affect vasoconstriction, cardiac contractility, and heart rate by increasing catecholamine levels. 7,8 In contrast, the vasopressive action of felypressin (an analogue of vasopressin) does not cause ischemic changes in the myocardium 9 and has lesser effects on circulatory dynamics than adrenaline.…”
mentioning
confidence: 99%
“…4 Dental local anesthetic solutions contain vasoconstrictors, for example, 2% lidocaine with 1:80,000 adrenaline (L þ AD) or 3% prilocaine with 0.03 IU/mL felypressin (P þ FP), are both commonly used in Japan and may potentially affect the cardiovascular condition. 5,6 L þ AD, which is one of the most frequently used anesthetics during dental treatment, is known to affect vasoconstriction, cardiac contractility, and heart rate by increasing catecholamine levels. 7,8 In contrast, the vasopressive action of felypressin (an analogue of vasopressin) does not cause ischemic changes in the myocardium 9 and has lesser effects on circulatory dynamics than adrenaline.…”
mentioning
confidence: 99%
“…Bader et al [ 4 ] reported that epinephrine concentrations of 1:80 000 and 1:100,000 in the dental local anesthetic cartridge are unnecessarily high. Because epinephrine is a hormone and a neurotransmitter, intra-operative over dose may cause elevated BP and HR due to stimulation of the sympathetic nerve system [ 15 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, felypressin is a synthetic hormone with similar properties to vasopressin. [ 15 ] In contrast to adrenaline, felypressin does not produce ischemia distal to or at the injection site. It is particularly suitable for use in patients for whom the use of solutions containing sympathomimetic agents is contraindicated.…”
Section: Introductionmentioning
confidence: 99%